(untitled) (The Research of Medical Science Review, 2025)
This research explores the effect of AI-driven algorithms on user engagement and media consumption trends within Over-The-Top (OTT) platforms. Online streaming services like Netflix, YouTube, and Amazon Prime are dominating the media landscape where AI personalization influences user behavior and to analyze changes in media consumption trends shaped by recommendation systems. PRISMA framework was adopted to analyze relevant peer-reviewed studies published between 2018 and 2025 and 26 articles were selected for review analysis based on inclusion/exclusion criteria. The literature reviewed reveals that AI algorithms greatly influence user engagement through personalizing content suggestions which increases satisfaction, enhances retention, and shifts users toward binge-watching. Furthermore, AI-driven personalization is found guiding users to content that aligns with their preferences, which raises concerns related to content diversity, filter bubble effects, and user awareness of algorithmic curation. This study contributes to a deeper understanding of how AI is shaping media consumption, offering both opportunities and challenges for users and content providers alike. This comprehensive review also identifies research gaps, such as the need for cross-platform comparisons and long-term behavioral studies which will provide valuable insights for future research.